2013
DOI: 10.1093/molbev/mst077
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeography of the Brown Bear (Ursus arctos) in Northeastern Asia Based on Analyses of Complete Mitochondrial DNA Sequences

Abstract: To further elucidate the migration history of the brown bears (Ursus arctos) on Hokkaido Island, Japan, we analyzed the complete mitochondrial DNA (mtDNA) sequences of 35 brown bears from Hokkaido, the southern Kuril Islands (Etorofu and Kunashiri), Sakhalin Island, and the Eurasian Continent (continental Russia, Bulgaria, and Tibet), and those of four polar bears. Based on these sequences, we reconstructed the maternal phylogeny of the brown bear and estimated divergence times to investigate the timing of bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
119
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(134 citation statements)
references
References 39 publications
10
119
4
Order By: Relevance
“…The timing of the split between brown and polar bears has been the subject of recent debates, with inferred dates ranging from~160,000 to~5 million years (Lindqvist et al 2010;Edwards et al 2011;Hailer et al 2012;Miller et al 2012;Cahill et al 2013; but see Ho et al 2008 andDavison et al 2011 for even younger estimates depending on the calibration method used). Compared with the mtDNA divergence estimate of 160,000 years between polar and brown bears (Lindqvist et al 2010;Edwards et al 2011;Hirata et al 2013), divergence times for the Y chromosome (>0.43 Ma, supplementary table S2, Supplementary Material online) are much older, confirming earlier suggestions that mtDNA has been introgressed (Hailer et al 2012Miller et al 2012;Cahill et al 2013). Compared with divergence times estimated from autosomal data, our 1.12 Ma estimate for brown/polar bear Y chromosomes ( fig.…”
Section: Speciation and Introgressionsupporting
confidence: 84%
See 1 more Smart Citation
“…The timing of the split between brown and polar bears has been the subject of recent debates, with inferred dates ranging from~160,000 to~5 million years (Lindqvist et al 2010;Edwards et al 2011;Hailer et al 2012;Miller et al 2012;Cahill et al 2013; but see Ho et al 2008 andDavison et al 2011 for even younger estimates depending on the calibration method used). Compared with the mtDNA divergence estimate of 160,000 years between polar and brown bears (Lindqvist et al 2010;Edwards et al 2011;Hirata et al 2013), divergence times for the Y chromosome (>0.43 Ma, supplementary table S2, Supplementary Material online) are much older, confirming earlier suggestions that mtDNA has been introgressed (Hailer et al 2012Miller et al 2012;Cahill et al 2013). Compared with divergence times estimated from autosomal data, our 1.12 Ma estimate for brown/polar bear Y chromosomes ( fig.…”
Section: Speciation and Introgressionsupporting
confidence: 84%
“…Polar bears exhibit low levels of population differentiation at biparentally inherited and mitochondrial markers throughout their range (Paetkau et al 1999;Cronin and MacNeil 2012;Miller et al 2012;Campagna et al 2013). Brown bears, in contrast, show considerable phylogeographic structuring at mitochondrial markers (Davison et al 2011;Edwards et al 2011;Hirata et al 2013;Keis et al 2013), and population structuring can also be discerned at biparentally inherited microsatellites (Paetkau et al 1997;Tammeleht et al 2010;Kopatz et al 2012). Most mtDNA clades are confined to certain geographical regions and are not shared between continents, although one brown bear clade is widespread throughout Eurasia and extends into North America (Korsten et al 2009;Davison et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, recent phylogeographic studies have shown that peripheral populations of Eurasian boreal mammals in areas such as the Kamchatka Peninsula and on Sakhalin, Hokkaido, and the southern Kuril Islands possess characteristic genetic structures compared to mainland populations (Iwasa et al 2000;Matsuhashi et al 2001;Inoue et al 2007;Iwasa et al 2009;Korsten et al 2009;Bannikova et al 2010;Davison et al 2011;Malyarchuk et al 2011;Abramson et al 2012;Kinoshita et al 2012;Ohdachi et al 2012;Yu et al 2012;Gus'kov et al 2013;Hirata et al 2013;Ishida et al 2013;Malyarchuk et al 2013). However, the unique colonization histories of these peripheral populations have not been sufficiently discussed in combination with the demographic population expansions that occurred on mainland Eurasia, with the exception of studies on a limited number of species (Iwasa et al 2000;Poyarkov and Kuzmin 2008;Korsten et al 2009;Davison et al 2011;Abramson et al 2012;Ohdachi et al 2012;Hirata et al 2013).…”
mentioning
confidence: 99%
“…In response to ever-increasing anthropogenic changes to natural ecosystems, genetic monitoring through the usage of different molecular markers is the best estimator of natural populations' sustainability, since genetic variability underpins populations' long-term potential for survival and adaptation (Palsbøll et al, 2007;Schwartz et al, 2007). Mitochondrial DNA is one of the most extensively used molecular markers in determining molecular diversity and phylogeography of many species (e.g., Castor fiber (Durka et al, 2005), Cervus elaphus (Zachos and Hartl, 2011), Sus scrofa (Alexandri et al, 2012;Veličković et al, 2015), Ursus actros (Hirata et al, 2013)), given the high evolutionary rate and lack of recombination (Avise, 2004). Even though analyses based solely on mtDNA have their own limitations due to mtDNA being a single locus marker with an effective population size of one-fourth of nuclear autosomal sequences, it is still a choice in preliminary analyses of genetic variability of wild populations.…”
Section: Introductionmentioning
confidence: 99%